Metabonomic analysis of abnormal sphingolipid metabolism in rheumatoid arthritis synovial fibroblasts in hypoxia microenvironment and intervention of geniposide - Ke, Jiang-Tao; Zhang, Heng; Bu, Yan-Hong; Gan, Pei-Rong; Chen, Fang-Yuan; Dong, Xin-Tong; Wang, Yan; Wu, Hong (Frontiers in Pharmacology, 2022)
Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by a joint hypoxic microenvironment. Our previous non-targeted metabolomics study found that sphingolipid (SPL) metabolism was abnormal in the joint synovial fluid samples from adjuvant arthritis (AA) rats. Geniposide (GE), an iridoid glycoside component of the dried fruit of Gardenia jasminoides J. Ellis, is commonly used for RA treatment in many Asian countries. At present, the mechanism of GE in the treatment of RA, especially in the joint hypoxic microenvironment, is not entirely clear from the perspective of SPL metabolism. The purpose of this research was to explore the potential mechanism of abnormal SPL metabolism in RA joint hypoxic microenvironment and the intervention effect of GE, through the targeted metabolic analysis based on the ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS). Arthritis index, foot swelling and histopathology were used to assess whether the AA rat model was successfully established. The SPLs extracts collected from AA rats’ synovial tissue, serum and rheumatoid arthritis synovial fibroblasts (RASFs, MH7A cells, hypoxia/normoxic culture) were analyzed by metabolomics and lipdomics approach based on UPLC-Q-TOF/MS, to identify potential biomarkers associated with disorders of GE regulated RA sphingolipid metabolism. As a result, eleven sphingolipid metabolites related to RA were screened and identified. Except galactosylceramide (d18:1/20:0), GE could recover the change levels of the above ten sphingolipid biomarkers in varying degrees. Western blotting results showed that the changes of ceramide (Cer) level regulated by GE were related to the down-regulation of acid-sphingomyelinase (A-SMase) expression in synovial tissue of AA rats. To sum up, this research examined the mechanism of GE in the treatment of RA from the perspective of SPL metabolism, and provided a new strategy for the screening of biomarkers for clinical diagnosis of RA.